2017
DOI: 10.1016/j.ajem.2017.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Regional disparities in the quality of stroke care

Abstract: The large quality gap in stroke care between metropolitan and non-metropolitan areas could be at least partly addressed through improved procedural efforts by stroke center certification increasing the supply of neurological services, (i.e. through training and hiring new neurologists) or by adopting decision support systems such as telemedicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 27 publications
1
34
0
2
Order By: Relevance
“…Receiving care at an approved stroke center, typically in metropolitan and non-rural areas, has improved both processes and outcomes for some minority patients experiencing a similarly time-sensitive health condition. 6668 Thus, adopting a similar ‘centers of excellence model’ for EGS care may both narrow the urban-rural divide in EGS care and augment EGS capacity across vulnerable populations irrespective of their county socio-demographic profiles. To do so, how ever, would require re-envisioning the Acute Care Surgery paradigm with a new scope of equity across the arena of EGS care .…”
Section: Discussionmentioning
confidence: 99%
“…Receiving care at an approved stroke center, typically in metropolitan and non-rural areas, has improved both processes and outcomes for some minority patients experiencing a similarly time-sensitive health condition. 6668 Thus, adopting a similar ‘centers of excellence model’ for EGS care may both narrow the urban-rural divide in EGS care and augment EGS capacity across vulnerable populations irrespective of their county socio-demographic profiles. To do so, how ever, would require re-envisioning the Acute Care Surgery paradigm with a new scope of equity across the arena of EGS care .…”
Section: Discussionmentioning
confidence: 99%
“…24 A recent study demonstrated a significant gap between metropolitan and nonmetropolitan area hospitals, especially with the rate of recombinant tissue plasminogen activator administration and provision of stroke education. 25 Even more alarming is that this rural-urban geographic disparity gap in rtPA use is increasing. 26 Several deficiencies contribute to the disparity in stroke care, including widespread geographic variation and access issues.…”
Section: Discussionmentioning
confidence: 99%
“…However, these patients lack the benefit of evidence-based triage criteria and verified centers of excellence that benefit patients with trauma, acute myocardial infarction (AMI), and ischemic stroke. That Americans experiencing acute chest pain, neurologic deficits, and injury benefit from robust systems of care targeting rapid evaluation and prompt triage for prompt intervention when needed has been shown to repeatedly reduce socioeconomic and demographic disparities in access to care and outcomes (HP Santry, unpublished data) 44–54. Investing resources to provide this kind of life-saving infrastructure and human capital at all hospitals is not feasible in the current landscape of general surgery.…”
Section: Introductionmentioning
confidence: 99%